Did K to 12 and COVID-19 as checkpoints lower down the Self-Efficacy of Undergraduate Cohorts? - Joebert D Ballesteros; Jun S Camara (ASEAN Multidisciplinary Research Journal, 2022)
Has COVID-19 pandemic lowered down the self-efficacy of then-K to 12 undergraduate cohorts? This study explored on the comparative mean level of confidence of undergraduates (n=990) of a large public state university in Pangasinan, Philippines, collected in the first quarter of 2022 using an adopted survey-questionnaire on General Self-Efficacy. Salient findings showed that the cohorts had an increase mean level of self-efficacy even during a pandemic compared with their cohort six years ago. Further, social self-efficacy received the highest mean while enlisting parental and community support recorded the lowest. This is in contrast with the cohort of 2016 which reported self-regulated learning and self-regulatory self-efficacy with highest and lowest means, respectively. Data analysis showed significant differences in both the means in terms of strand and field of specialization in the cohort 2016 and 2022, respectively. Further, statistical analysis revealed that the difference in mean self-efficacy of both cohorts is significant at both 0.05 and 0.01 level of alpha. The researchers concluded that COVID-19 did not lower down the self-efficacy of undergraduates in learning in higher education institutions in the Philippines, based on the sample taken. Further, data suggest that the implementation of flexible learning even during post-pandemic period could be sustained in the perspective of the students. However, this study recommends that those HEIs which opt to continue Flexible Learning should assess or re-assess their readiness for its sustained implementation.